Effects of different dietary energy and protein levels on the performance and carcass characteristics of native hilly chicken during growing phase in confinement (Asian-Australasian Journal of Bioscience and Biotechnology, 2021)
Two hundred and sixteen 10 weeks of age hilly chickens were used to determine the effects of dietary energy and protein level on growth performance, carcass characteristics and meat quality. The chicks were randomly allotted in to 3×3 factorial in a completely randomize design. Three levels of energy (2600, 2700 and 2800 ME kcal/kg) and three levels of dietary proteins (16, 17 and 18% CP) were offered ad libitum to the chicks from 10-16 weeks of age. There were no significant interaction effect between dietary protein and energy levels in the diets. At 10-16 weeks of age hilly chickens fed with the medium protein diet (17% CP) showed shortened feed intake (p